Prospects of Digital Literature and Its Implications on Increasing Learning Outcomes During The Covid-19 Pandemic - Samsul Susilawati (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The implementation of the Education Policy in the Covid-19 Emergency Period requires educators to carry out a learning innovation, namely self-directed learning based on digital literacy. This progress has presented both challenges and opportunities for human life. Humans can enjoy the convenience of accessing information and can enjoy the facilities of digital technology freely. Digital literacy needs to be developed in the world of education today to improve student learning outcomes. The purpose of this research is to determine the effect of the application of digital literacy on improving the learning outcomes of students of the Social Science Education Department, Faculty of Tarbiyah and Teacher Training, in the Development of Learning Resources and Media Courses at UIN Maulana Malik Ibrahim Malang. This research uses quantitative methods with a simple linear regression approach. The research data were collected through questionnaires and documentation. The questionnaire was distributed to 77 samples from 152 populations with the sampling technique using purposive sampling. Based on the results of the study, it was obtained R of 0.667, which indicates that the relationship between the application of digital literacy (variable X) and learning outcomes (Variable Y) is strong. The results of the F test prove that F 68,688> F 4.39, then the alternative hypothesis (H) is accepted and the null hypothesis (H) is rejected. The results and conclusions of this study indicate that the application of digital literacy has an influence on improving student learning outcomes.